NUTRITION – A FACTOR OF HEALTH, FOOD SAFETY - Ikramova Nargiza Alisher qizi; Jabborova Durdona Baxtiyor qizi; Abdunazarova Gulhayo Shamsiddin qizi (Modern American Journals, 2025)
This study provides a comprehensive analysis of the hygienic and physiological significance of nutrition in human health and social life. Nutrition, as a key factor ensuring the vital processes of the organism, maintains the balance between assimilation and dissimilation. The human body’s need for energy and nutrients is met through proteins, fats, carbohydrates, vitamins, and mineral salts. The paper also analyzes the causes and consequences of alimentary diseases (such as obesity, avitaminosis, and protein-energy deficiency) resulting from improper and insufficient nutrition.
Keywords: Nutritional hygiene; rational nutrition; physiological standards; nutrient balance; alimentary diseases; healthy lifestyle; food culture; public health in Uzbekistan; physical development; medical care; hygienic norms; dietary intake; energy from fats; carbohydrate metabolism; vitamin activity.